PENGARUH PENYAJIAN LAPORAN KEUANGAN YANG JELAS TERHADAP PENGAMBILAN KEPUTUSAN INVESTASI: PENDEKATAN KUANTITATIF - Ivanza, Amanda Ridho Ivanza; Ersi Sisdianto (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
Examining the impact of transparent financial statement presentation on capital market investment decision-making is the goal of this study. Investment choices play a significant role in determining the course of an organization's and the economy's overall economic growth. Financial statements that are presented in a clear, comprehensive, and transparent manner are thought to be an efficient way to give investors trustworthy information. This study determines the degree to which elements in transparent financial statements affect investment choices using a quantitative methodology that includes survey techniques and regression analysis. Based on the information at hand, policymakers, businesses, and investors should be able to make better decisions thanks to the study's deeper insights